The effects of prenatal GenX (HFPO-DA) exposure on gut microbiota and metabolic function in pregnant rats and their offspring - Han, Wenchao; Zhang, Xinpeng; Li, Dan; Liu, Wendong; He, Yanxia; Shang, Haitao; Yang, Zhugen; Liu, Hongyun; Zhu, Wenjing (Elsevier, 2026)
Hexafluoropropylene oxide dimer acid [(HFPO-DA), GenX] is listed as Substances of Very High Concern (SVHC) by the Commission of Member States (MSC) in 2019. The threat of GenX to human health, especially to sensitive populations such as pregnant women, infants and children cannot be ignored. We aimed to investigate the effects of GenX on the intestinal barrier function and gut microbiota of both pregnant rats and their offspring. We subsequently performed a metabolomic analysis of the maternal gut to investigate the metabolic disruptions associated with GenX exposure. Pregnant Sprague-Dawley rats (n = 12/group) received GenX once daily by gavage at 0, 1, 10, or 100 mg/kg body weight from gestational day (GD) 0.5 through GD 19.5. We observed intestinal tissue damage and changes in the gut microbiota in both pregnant rats and their offspring. Additionally, we performed untargeted LC/MS metabolomic analysis on the intestinal tissues of the pregnant rats. The intestinal barrier function of the pregnant rats was impaired. The results of 16S rRNA gene sequencing indicate that GenX alters the gut microbiota diversity and composition in both pregnant rats and their offspring. The metabolites of pregnant rats were also found to be significantly altered, and these metabolites are mainly associated with amino acid metabolism, carbohydrate metabolism, and lipid metabolism. Collectively, Exposure to GenX disrupts the intestinal barrier function of pregnant rats, exacerbates microbiome toxicity, and disturbs the gut microbiome-metabolome homeostasis.
Keywords: 3205 Medical Biochemistry and Metabolomics; 31 Biological Sciences; 32 Biomedical and Clinical Sciences; 3107 Microbiology; Women's Health; Perinatal Period - Conditions Originating in Perinatal Period; Microbiome; Nutrition; Pediatric; Pregnancy; Digestive Diseases; 1.1 Normal biological development and functioning; 2.1 Biological and endogenous factors; Oral and gastrointestinal; Environmental Sciences